(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Socio-economic and environmental impacts analysis of shrimp (Paeneus monodon) farming in the gher area of Bagerhat District is an important aspect where shrimp cultivation increased over the years. An investigation was conducted to evaluate the present socio-economic status as well as to investigate the soil and water quality of the study area. This study has been carried out at ten villages in five Upazilla (Bagerhat Sadar, Rampal, Mangla, Chitalmari and Fakirhat) of Bagerhat District. The socio-economic impact was investigated using questionnaire survey and environmental impact was assessed by analyzing water and soil quality. The soil and water samples were collected during the period of January to March 2013. Maximum people of this study area were involved in shrimp culture because soil is not suitable for agricultural crops due to high salinity percentage. Annual family income of maximum number (45%) of farmers was greater than 200000 taka per year from shrimp culture. All the soil pH value was neutral to slightly alkaline. Shrimp culture has no noticeable impact on soil quality. On the other hand, shrimp culture has some negative impacts on water quality such as, the range of K and Na in water has been increased and the range of Ca has been decreased than normal range. However, it is very minor compared to annual income from this culture. Therefore, the people of this region may involve more in shrimp culture. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22181 J. Environ. Sci. & Natural Resources, 7(1): 265-269 2014